Efforts to Improve the Ability to Read the Qur'an Using the WAFA Book Method at Usman Al-Farsy Plus Kindergarten - Nurul Arifin, Rifatul Hasanah; Dewi Pusparini; Khozaimah; Ani Fitriyah; Robiatul Adawiyah; Qurrotul Uyun (STIT Attaqwa, 2025)
This study aims to improve the ability to read the Qur'an of early childhood children in Usman Al-Farsy Plus Kindergarten through the application of the Wafa book method. This method uses the Quantum Teaching approach that integrates multisensory-based learning, such as songs, movements, and visual aids. This study uses the Classroom Action Research (CAR) model with the Kemmis and Taggart design, involving 22 children in group A as research subjects. The results showed a significant increase in the ability to read the Qur'an after the application of the Wafa book method. In the pre-cycle, only 27% of children reached the